Implementación de un proceso contable y tributario en la empresa automotriz blacio, periodo del 01 de julio al 31 de diciembre del 2019 - García Hualpa, Rebeca del Cisne (2022)
The development of the following thesis, called "IMPLEMENTATION OF AN ACCOUNTING AND TAX PROCESS IN THE COMPANY AUTOMOTRIZ BLACIO, PERIOD FROM JULY 1 TO DECEMBER 31, 2019", was executed with the purpose of implementing an accounting and tax process in order to to have a tool to control financial resources, to contribute to the decision-making of the company. To meet the objectives set and to implement accounting in the commercial company "AUTOMOTRIZ BLACIO", it began with the design of the plan and manual of accounts codified and ordered according to the needs of the company; then proceeded to collect information, starting with the supporting documents that allowed to carry out the accounting record, initial inventory, observing the goods, values and obligations of the company, based on the collection of the aforementioned documents, sales and purchasing assistants were carried out , plan and account manual with their respective debit, credit and balance. In accordance with the objectives set, the accounting process was developed starting with the writing of the memorandum of operations based on the activities carried out during the accounting year, supported by source documentation, since with this the record in the Daily Book began of the accounting entries, the Majorization of each of the accounts resulting from the exercise was made to continue with the Trial Balance, the Worksheet, the respective Adjustments, which facilitated the preparation of the Financial Statements such as: Income Statement, Statement of Financial Position and Statement of Cash Flow, which allowed evaluating the financial and economic performance of the company and decision-making. To conclude, with the application of financial indicators, it was possible to know the real situation of the company, whose result is not economically favorable. However, with correct decision-making, it will allow to improve the organization and control of operations, which come from reliable information on the economic situation, focused on its development. Thus, with the accounting implementation applied in the commercial company "AUTOMOTRIZ BLACIO", it was possible to carry out adequate control and organization of the economic activities of the company, obtaining clear and orderly information reflected in the financial statements, where a loss was determined. net of the year.